2009
DOI: 10.1007/s00432-009-0664-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of targeted therapy in patients with renal cell carcinoma with pre-existing or new bone metastases

Abstract: Further evaluation of the effect of these therapies on bone metastases in RCC is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…One retrospective study suggested that targeted agents appeared slightly more effective than cytokine therapy at extending mean time to progression of pre-existing bone lesions [23]. On the other hand, in prospective clinical trials, interestingly, the efficacy of targeted agents was apparently not affected by prior cytokine treatment.…”
Section: Discussionmentioning
confidence: 97%
“…One retrospective study suggested that targeted agents appeared slightly more effective than cytokine therapy at extending mean time to progression of pre-existing bone lesions [23]. On the other hand, in prospective clinical trials, interestingly, the efficacy of targeted agents was apparently not affected by prior cytokine treatment.…”
Section: Discussionmentioning
confidence: 97%
“…The bone marrow microenvironment possesses extensive hypoxic regions [42, 43] that are characterized by abundant HIF-1α staining and HIF target proteins including MCT4 and Glut1 [44]. It’s notable that the hypoxic microenvironment of the bone marrow is conductive to subsequent bone colonization of cancer cells, and therapies targeting HIF/HIF targets has potential value in the prevention of bone colonization [6062]. Furthermore, accumulating studies revealed that miRNAs are emerging as a novel class targets of hypoxia-responsive molecules [63, 64].…”
Section: Discussionmentioning
confidence: 99%
“…Sunitinib, a small molecule inhibitor targeting VEGF receptor (VEGFR) and platelet-derived growth factor receptor β (PDGFRβ), is more effective than interferon-α or sorafenib, a chemical kinase inhibitor that targets VEGFR and PDGFRβ, at blocking the formation and time to occurrence of osteolytic lesions in bone metastatic renal cell carcinoma (RCC) patients (Zolnierek et al, 2010), likely due to the high extent of vascularization observed in RCC bone metastases. A retrospective study reported that the RCC patient long-term responders to sunitinib had lower odds of having a bone metastasis (Molina et al, 2013), and thus these patients already had a better prognosis and less aggressive disease.…”
Section: Therapeutic Potential Of Hif Targets In Bone Metastasismentioning
confidence: 99%